2011
DOI: 10.1007/bf03404193
|View full text |Cite
|
Sign up to set email alerts
|

Impacting Canadian Public Health Nurses’ Job Satisfaction

Abstract: he public health sector is experiencing recruitment and retention issues similar to those in other areas of the Canadian health system; the current workforce is aging and replacing and retaining such expertise is challenging. 1-3 Job dissatisfaction has been linked to retention issues, absenteeism, increased costs, and ultimately diminished client outcomes. 4-6 As nurses constitute the largest professional group of national public health human resources, 1,3,7 it would be beneficial to gain a better understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 10 publications
4
38
0
Order By: Relevance
“…This case study confirms one of the major conclusions of the published literature, namely the sources of job satisfaction (Baldwin et al., ; Curtis & Glacken, ; Graham et al., ; Haugh & Laschinger, ; Keller et al., ). It is clear that job satisfaction is an outgrowth of an organizational structure which concentrates on three key issues—the communications between the ranks of the hierarchy `which the organizational structure encourages/discourages, the physical working environment it provides, and the resources it furnishes workers to meet the demands laid on them.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…This case study confirms one of the major conclusions of the published literature, namely the sources of job satisfaction (Baldwin et al., ; Curtis & Glacken, ; Graham et al., ; Haugh & Laschinger, ; Keller et al., ). It is clear that job satisfaction is an outgrowth of an organizational structure which concentrates on three key issues—the communications between the ranks of the hierarchy `which the organizational structure encourages/discourages, the physical working environment it provides, and the resources it furnishes workers to meet the demands laid on them.…”
Section: Resultssupporting
confidence: 83%
“…Best and Thurston's () sample also singled out autonomy and wages as factors in job satisfaction, together with direct contact with clients. Similar findings on professional status, autonomy and workload variables as predictors of job satisfaction were reported in later studies (Curtis & Glacken, ; Graham et al., ).…”
Section: Literature Reviewsupporting
confidence: 86%
See 1 more Smart Citation
“…Although a number of articles identified in this review have confirmed significant relationships between work related stressors and burnout [25,26,27,28,29,30,31,32,33,34,59,60,77,78], job satisfaction [11,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,58,59,60,61,62,63,64,65,66,81] as well as general health, these relationships are predominantly two way relationships with only a handful of studies confirming three way relationships [64,65,71,84]. Among the studies confirming two way relationships, only one study confirming the relationship between job satisfaction and general health [85] was identified.…”
Section: Discussionmentioning
confidence: 91%
“…Work related stressors including pay, task requirements, well maintained up to date resources [36,37,38], physical work environment [39], autonomy [40,41,42], peer relationships, cohesion, feedback [40,41,43], workload, control over practice [44,45] patient outcomes and supervisor support [36,41] recognition, independence, responsibility, authority [46], meaningfulness of work, nurse centered communication involving humor and clarity [47], role stress [48] as well as overtime [38,41] were related to job satisfaction. It has also been found that the interaction between workload and autonomy best predicts job satisfaction [44]. A common conclusion was that work related stress is significantly related to job satisfaction [49,50] and nurses who experience higher stress levels are less satisfied with their jobs [51].…”
Section: Resultsmentioning
confidence: 99%